Impact of payments for environmental services and protected areas on local livelihoods and forest conservation in northern Cambodia. Issue 1 (9th December 2014) - Clements, Tom; Milner‐Gulland, E. J.
Abstract The potential impacts of payments for environmental services (PES) and protected areas (PAs) on environmental outcomes and local livelihoods in developing countries are contentious and have been widely debated. The available evidence is sparse, with few rigorous evaluations of the environmental and social impacts of PAs and particularly of PES. We measured the impacts on forests and human well‐being of three different PES programs instituted within two PAs in northern Cambodia, using a panel of intervention villages and matched controls. Both PES and PAs delivered additional environmental outcomes relative to the counterfactual: reducing deforestation rates significantly relative to controls. PAs increased security of access to land and forest resources for local households, benefiting forest resource users but restricting households' ability to expand and diversify their agriculture. The impacts of PES on household well‐being were related to the magnitude of the payments provided. The two higher paying market‐linked PES programs had significant positive impacts, whereas a lower paying program that targeted biodiversity protection had no detectable effect on livelihoods, despite its positive environmental outcomes. Households that signed up for the higher paying PES programs, however, typically needed more capital assets; hence, they were less poor and more food secure than other villagers. Therefore, whereas the impacts of PAs on household well‐being were limited overall and varied between livelihood strategies, the PES programs had significant positive impacts on livelihoods for those that could afford to participate. Our results are consistent with theories that PES, when designed appropriately, can be a powerful new tool for delivering conservation goals whilst benefiting local people.